Overlapping dose responses of spermatogenic and extragonadal testosterone actions jeopardize the principle of hormonal male contraception. Issue 6 (5th March 2014) - Oduwole, Olayiwola O.; Vydra, Natalia; Wood, Nicholas E. M.; Samanta, Luna; Owen, Laura; Keevil, Brian; Donaldson, Mandy; Naresh, Kikkeri; Huhtaniemi, Ilpo T.
ABSTRACT: Testosterone (T), alone or in combination with progestin, provides a promising approach to hormonal male contraception. Its principle relies on enhanced negative feedback of exogenous T to suppress gonadotropins, thereby blocking the testicular T production needed for spermatogenesis, while simultaneously maintaining the extragonadal androgen actions, such as potency and libido, to avoid hypogonadism. A serious drawback of the treatment is that a significant proportion of men do not reach azoospermia or severe oligozoospermia, commensurate with contraceptive efficacy. We tested here, using hypogonadal luteinizing hormone/choriongonadotropin receptor (LHCGR) knockout ( LHR –/– ) mice, the basic principle of the T‐based male contraceptive method, that a specific T dose could maintain extragonadal androgen actions without simultaneously activating spermatogenesis. LHR –/– mice were treated with increasing T doses, and the responses of their spermatogenesis and extragonadal androgen actions (including gonadotropin suppression and sexual behavior) were assessed. Conspicuously, all dose responses to T were practically superimposable, and no dose of T could be defined that would maintain sexual function and suppress gonadotropins without simultaneously activating spermatogenesis. This finding, never addressed in clinical contraceptive trials, is not unexpected in light of the same androgen receptor mediating androgen actions in all organs. When extrapolated to humans, our findings may jeopardize the current approach to hormonal male contraception and call for more effective means of inhibiting intratesticular T production or action, to achieve consistent spermatogenic suppression.—Oduwole, O. O., Vydra, N., Wood, N. E. M., Samanta, L., Owen, L., Keevil, B., Donaldson, M., Naresh, K., Huhtaniemi, I. T. Overlapping dose responses of spermatogenic and extragonadal testosterone actions jeopardize the principle of hormonal male contraception. FASEB J . 28, 2566–2576 (2014). www.fasebj.org